ENT 530 Facebook Report : "Bronis Legend" / Nur Izaty Syafiqah Idris - Idris, Nur Izaty Syafiqah (2018)
his is sole proprietorship type of business. This company owned by me. I am selling a product which is Bronis Legend. I as a agent of the Bronis Legend. I took the stock from my friend. She is the supplier of Bronis Legend to me. I created a facebook page named "Bron is Legend". I updated the facebook page frequently. In the facebook content consist of teaser, soft sell and hard sell. Firstly, I posted the teasers such as stay tuned, I am coming, and so on. This is to make my customer wondering what kind of product that I am selling. This will make a sense of curiosity to my customer on what I am going to introduce. The total of teaser is about 7 teasers. Next, I am posted soft sell which include the advantages of my product also the information on my product.